The consequences of the choice of design standards for the use of material on the example of reinforced concrete flat ceiling - Kargol, Wioleta; Szerafin, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
In connection with the unification of Polish Construction Standards with their European counterparts, which takes place after the entry of our country in the European Union structure, it’s time to replace the Polish Building Standards with Eurocode counterparts. These changes are the cause of anxiety in the designer circle, caused by changes in the procedures of design, the volume of European standards and the fear that the new standards of design produce a more economically unfavorable results. The article presents the changes by standards relevant to the design of reinforced concrete flat slab and plate sample calculation results and their analysis.